2018
DOI: 10.3390/ma11101973
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant/Antibacterial Electrospun Nanocoatings Applied onto PLA Films

Abstract: Polylactic acid (PLA) films were coated by coaxial electrospinning with essential and vegetable oils (clove and argan oils) and encapsulated into chitosan, in order to combine the biodegradability and mechanical properties of PLA substrates with the antimicrobial and antioxidant properties of the chitosan–oil nanocoatings. It has been established that the morphology of the electrospun nanocoatings mainly depend on the average molecular weight (MW) of chitosan. Oil beads, encapsulated into the main chitosan nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…Munteanu et al investigated the biodegradation and tensile properties of PLA membranes coated with antimicrobial and antioxidant CS-EO complexes [136]. Chitosan has exhibited significant antibacterial action against various pathogens such as Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa [137]; therefore, it has been a popular subject of studies in antibacterial coatings [138].…”
Section: Encapsulation Of Eugenol Essentialmentioning
confidence: 99%
“…Munteanu et al investigated the biodegradation and tensile properties of PLA membranes coated with antimicrobial and antioxidant CS-EO complexes [136]. Chitosan has exhibited significant antibacterial action against various pathogens such as Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa [137]; therefore, it has been a popular subject of studies in antibacterial coatings [138].…”
Section: Encapsulation Of Eugenol Essentialmentioning
confidence: 99%
“…The antimicrobial activity of plant essential oils is attributed to their chemical structure, in particular the presence of hydrophilic functional groups, such as hydroxyl groups of phenolic components and/or lipophilicity of some essential oil components [20]. To overcome the essential oils volatility, different formulation techniques and methods have been developed, such as casting [21], emulsion ionic gelation [22] or encapsulation by electrospinning [23].…”
Section: Introductionmentioning
confidence: 99%
“…Munteanu et al [ 259 ] prepared a nanocoating by encapsulating argan and clove oils into chitosan by coaxial electrospinning and then used it to functionalize electrospun PLA materials previously treated with CPT. The authors concluded that the electrospun coaxial encapsulation of clove and argan oils into chitosan led to enhanced antimicrobial activity against E. coli , S. typhymurium , and L. monocytogenes .…”
Section: Polyestersmentioning
confidence: 99%